Outcomes of Percutaneous Peritoneal Dialysis Catheters Insertion by Interventional Radiologists: A Single-Institution Experience - Khadijah Alhussaini; Shaima Abulqasim; Abdulaziz Mohammad Al-Sharydah; Elwaleed Elhassan; Mohammad Arabi (The Arab Journal of Interventional Radiology)
Objectives This article evaluates the short- and long-term outcomes of percutaneous peritoneal dialysis (PD) catheters inserted by interventional radiology service and analyzes the factors that affect the sustainability of patent and functional PD catheters. Materials and Methods Retrospective single-institution study between April 2015 and February 2021. A total of 131 patients (75 males) were enrolled with mean age of 50 ± 19.6 years with an average body mass index (BMI) of 28 ± 7 kg/m2. Technical and clinical success were evaluated. Catheter-related complications were classified into mechanical and nonmechanical categories, including infectious complications. Indications for removal were analyzed. Results Technical and clinical success were 100%. The average dwelling time for the entire cohort was 497.5 ± 462.3 days. Forty-six patients (35%) were on PD at the last follow-up with an average dwelling time of 492 days. PD-related complications were reported in 79/131 (60.3%) patients, including peritonitis (40.46%; 53/131), followed by malposition/migration (12.21%; 16/131), tunnel/exit site infection (10.69%; 14/131), and dysfunction (12.21%; 16/131). The incidence of peritonitis within 30 days postinsertion was 9.43% (5/53). The average interval between insertion and migration was 100.5 ± 144.8 days (95% confidence interval, 6.9–14.4). There was a trend for a higher rate of malposition/migration in patients with higher BMI (p = 0.0561). Causes for PD catheters removal were: (1) infection-related (24.4%; 32/131), (2) renal transplant recipients (16%; 21/131), (3) mechanical complications (13.7%; 18/131), and (4) patient's preference (7.6%; 10/131). Conclusion Percutaneous PD catheter placement by interventional radiologists provides acceptable long-term outcomes and complication rates that meet the recommended standards.